Africa : Adjustment to the Challenges of Globalization. (International Monetary Fund, 1999)
Sub-Saharan Africa needs much faster economic growth and more effective economic, financial, and social policies if it is to make up for lost ground and reduce the number of people living in abject poverty. Edited by Laura Wallace, this volume presents the proceedings of a May 1998 seminar in Paris, organized jointly by the IMF and the Japanese Ministry of Finance, on ways to accelerate Africa's growth in our increasingly globalized world. Senior African and Asian government officials, representatives from multicultural institutions, donors, academics, and private sector participants gathered to discuss how to improve the private investment environment in African countries and take advantage of globalization's benefits while minimizing its risks, and how to strengthen the contribution of government in areas of capacity building, good governance, effective public resource management, and improved quality and composition of government spending.